T cell heterogeneity in asthma pathogenesis: from immunological mechanisms to biological targeted therapies - Gan, Qifeng; Zhu, Yuzhen; Guo, Yuxin; Fu, Guo; Zhang, Xiao-Bin (Frontiers in Immunology, 2025)
Severe and overlapping asthma endotypes—particularly steroid-insensitive disease—remain undertreated, highlighting the need for a T-cell–centered synthesis. This review frames asthma heterogeneity through the interplay of T-cell axes, with Th2 pathways shaping T2-high disease and Th17/Treg imbalance characterizing T2-low features and much of steroid resistance. Building on this framework, we map therapies to mechanism: IL-4Rα and IL-5/IL-5R blockade chiefly mitigate Th2-dominated circuits, whereas upstream alarmin inhibition (e.g., TSLP) modulates epithelial–immune cues that influence both T2-high biology and selected T2-low processes. We then outline what is needed to translate mechanisms into decisions—integrated biomarkers to refine endotypes and mechanism-guided switching or combinations, with emphasis on T2-low populations where unmet need is greatest. By linking T-cell biology to therapeutic leverage points, the review offers a concise path from mechanism to patient stratification and more rational treatment choices.